Publication Frequency and Google Trends Analysis of Popular Alternative Treatments to Arthritis - Neil Pathak, MD; Zachary J. Radford, MD; Joseph B. Kahan, MD, MPH; Jonathan N. Grauer, MD; Lee E. Rubin, MD (Arthroplasty Today, 2022)
Background: Public interest in alternative, nonoperative treatments for the management of arthritis has increased. Few have been approved by the Food and Drug Administration. The present study aimed to evaluate trends in public and scientific interest in 4 such treatments by assessing Google Trends and publication frequency data, respectively. Material and methods: Turmeric, stem cell therapy, platelet-rich plasma (PRP) therapy, and cannabidiol (CBD) were studied. For 2010-2019, Google Trends data and publication frequency data on PubMed were collected by year for arthritis and each of the 4 therapies. Linear, quadratic, and exponential regressions were applied, and the best model of growth was identified. Results: From 2010 to 2019, Google Trends annual scores for arthritis and turmeric (exponential; R2: 90.5%, P < .001), CBD (exponential; R2: 99.3%, P < .001), stem cell therapy (exponential; R2: 86.7%, P < .001), and PRP therapy (linear; R2: 80.6%, P < .001) increased significantly. Search term frequencies for arthritis and CBD exhibited the highest increase (12,929%). Publications in arthritis and turmeric (linear; R2: 74%, P = .001), stem cell therapy (linear; R2: 94.8%, P < .0001), and PRP therapy (linear; R2: 97.1%, P < .0001) increased from 2010 to 2019. However, publications relating to arthritis and CBD have not increased (P = .122). Conclusion: Regression analysis indicates that public interest in alternative therapies have had a marked increase. The rise in public interest for CBD, and to a lesser extent, turmeric, stem cell therapy, and PRP, has dramatically outstripped scientific evidence on these therapies. Rigorously designed, clinical studies may be beneficial to keep up with the growing popularity of these treatments, especially CBD.